The prevalence of vitamin A deficiency and its public health significance in children in low- and middle-income countries: A systematic review and modelling analysis - Song, Peige; Adeloye, Davies; Li, Shuting; Zhao, Dong; Ye, Xinxin; Pan, Qing; Qiu, Yiwen; Zhang, Ronghua; Rudan, Igor (Journal of global health, 2023)
Vitamin A deficiency (VAD) is widely recognised as a major public health concern in low- and middle-income countries (LMICs). Despite various interventions implemented in many countries, a lack of reliable data is hindering progress. We aimed to consolidate available data and quantify estimates of the prevalence of VAD among children ≤18 years in LMICs. We searched PubMed, Medline and Embase for studies reported the prevalence of VAD or marginal (m)VAD among children. A multilevel mixed-effects meta-regression approach was applied to establish the regression models for VAD and mVAD prevalence. The total numbers of children affected by VAD and mVAD in LMICs in 2019 were separately calculated from the estimated age- and socio-demographic index (SDI)-specific prevalence with their corresponding United Nations Population Division populations projections. We estimated areas of significant public health concern in 165 LMICs using the lower confidence interval (CI) of VAD prevalence. A total of 116 articles from 40 LMICs were retained. In 2019, VAD and mVAD affected 333.95 million (95% CI = 253.00-433.74) and 556.13 million (95% CI = 388.83-767.94) children and adolescents in 165 LMICs, respectively, corresponding to a prevalence of 14.73% (95% CI = 11.16-19.14) and 24.54% (95% CI = 17.15-33.88). The prevalence of both VAD and mVAD was the highest in children aged 0-5 years at 19.53% (95% CI = 15.03-24.91) and 28.22% (95% CI = 20.00-38.24), respectively, with both steadily decreasing to 10.09% (95% CI = 7.44-13.50) and 20.76% (95% CI = 14.16-29.50) in adolescents aged 13-18 years. The prevalence of VAD was significantly higher in the low SDI region at 29.67% (95% CI = 22.67-37.53) compared to 5.17% (95% CI = 3.14-8.43) estimated in the high-middle SDI region. 68 of the 165 LMICs (41.21%) were classified as areas of moderate to severe VAD public health significance. VAD continues to pose a significant public health concern in many low-income settings. Development in LMICs is a crucial factor for VAD, with a disproportionately higher burden in low SDI regions. This study protocol was registered with PROSPERO, CRD42020220654.